2021
DOI: 10.3390/ijms22031148
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Changes in Three Brain Regions during Chronic Lithium Administration in the Rat Models of Mania and Depression

Abstract: Lithium has been the most important mood stabilizer used for the treatment of bipolar disorder and prophylaxis of manic and depressive episodes. Despite long use in clinical practice, the exact molecular mechanisms of lithium are still not well identified. Previous experimental studies produced inconsistent results due to different duration of lithium treatment and using animals without manic-like or depressive-like symptoms. Therefore, we aimed to analyze the gene expression profile in three brain regions (am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Previous preclinical studies showed that lithium reversed hyperactivity and risktaking behavior after repeated injections of amphetamine [107,108], and thus was considered a validated model of mania in rats [109][110][111]. Therefore, studies using this model of mania confirmed that lithium prevented the amphetamine-induced inhibition of ETC complexes I, II, III, and IV in the hippocampus, striatum and prefrontal cortex.…”
Section: Lithium Influences Inflammation and Energy Metabolismmentioning
confidence: 85%
“…Previous preclinical studies showed that lithium reversed hyperactivity and risktaking behavior after repeated injections of amphetamine [107,108], and thus was considered a validated model of mania in rats [109][110][111]. Therefore, studies using this model of mania confirmed that lithium prevented the amphetamine-induced inhibition of ETC complexes I, II, III, and IV in the hippocampus, striatum and prefrontal cortex.…”
Section: Lithium Influences Inflammation and Energy Metabolismmentioning
confidence: 85%
“…Neurobiological studies have confirmed that the occurrence of depression is related to multiple brain regions [34,35], mainly the prefrontal cortex (PFC), anterior cingulate cortex (ACC), thalamus, hippocampus, amygdala, and basal ganglia. Damage to the hippocampus is considered to be closely related to depression, posttraumatic stress disorder, and other mental diseases.…”
Section: Discussionmentioning
confidence: 99%